Effect of anaerobic digestion and initial pH on metal bioleaching from sewage sludge - Villar, L. D.; Garcia, O. (Taylor & Francis Inc, 2006)
The effects of anaerobic digestion and initial pH on the bioleaching of metals from sewage sludge were investigated in shake flask experiments. A strain of Acidithiobacillus thiooxidans was employed in the assays using secondary and anaerobic sludges, which resulted in similar solubilization yields of the metals chromium, copper, lead, nickel, and zinc for both the sludges investigated. The effect of initial pH (7.0 and 4.0) on metal bioleaching was assayed by using the anaerobic sludge inoculated with indigenous sulfur-oxidizing thiobacilli. Although the time required to reach the end of the experiment (final pH close to 1.0) was shortened at initial pH of 4.0, final metal solubilization was not significantly different for both initial pH values, resulting in higher solubilization yields for copper, nickel, and zinc (higher than 80%). Chromium and lead presented solubilization yields close to 50%. The results obtained in this work showed that the metal bioleaching process can be applied to sewage sludge regardless of the type of sludge and without the requirement of pH adjustment.
Keywords: bacterial leaching; metals; sewage sludge; sulfur; Thiobacillus